Highly Pathogenic Avian Influenza A(H5N1) Mutants Transmissible by Air Are Susceptible to Human and Animal Neutralizing Antibodies - Du, Lanying (Oxford University Press, 2013)
A laboratory-generated reassortant H5 hemagglutinin (HA)/influenza A(H1N1) strain containing 4 mutations in influenza A(H5N1) HA has become transmissible by air among mammals. Here, we constructed 15 influenza A(H5N1) pseudoviruses containing a single mutation or a combination of mutations and showed that the pseudoviruses were susceptible to neutralizing antibodies from patients with influenza A(H5N1) infection and from mice immunized with a vaccine containing the conserved HA1 sequence of influenza A(H5N1). These results indicate that antibodies in patients currently infected by influenza A(H5N1) and antibodies induced by vaccines containing conserved sequences in HA1 of wild-type influenza A(H5N1) are highly effective in cross-neutralizing future influenza A(H5N1) mutants with airborne transmissibility, suggesting that human influenza pandemics caused by these influenza A(H5N1) variants can be prevented.